A common evolutionary origin reveals fundamental principles of protein insertases - Vögtle, Friederike-Nora; Koch, Hans-Georg; Meisinger, Christof (PLoS biology, 2022)
Membrane proteins require protein machineries to insert their hydrophobic transmembrane domains (TMDs) into the lipid bilayer. A functional analysis of protein insertases in this issue of PLOS Biology reveals that the fundamental mechanism of membrane protein insertion is universally conserved.
Gesehen am 28.06.2022